2008
DOI: 10.3171/ped.2008.2.12.386
|View full text |Cite
|
Sign up to set email alerts
|

Translaminar screw fixation in the subaxial pediatric cervical spine

Abstract: The use of spinal instrumentation to stabilize the occipitocervical junction in pediatric patients has increased and evolved in recent years. Wiring techniques have now given way to screw-rod or screw-plate techniques with or without postoperative external immobilization. Although C-2 translaminar screws have been used in these constructs, subaxial translaminar screws have not, to date, been described in either the pediatric or adult patient populations. The authors describe the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…20,[25][26][27] Studies have also shown the applicability of this technique in the subaxial cervical spine and the thoracic region. 3,5,11,12,14,15 Although cadaveric and CT-based analyses have been performed to assess the feasibility of TLS placement at C-2, there is limited information in the literature regarding the critical proportions of the upper thoracic laminae as they relate to the use of TLS. 2,7,24 In this study, CT scans were used to estimate screw size and placement in the upper thoracic spine, and we found that the average estimated TLS screw length at T-1 (33.4 mm) was 5.8 mm longer than at T-2 (27.6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…20,[25][26][27] Studies have also shown the applicability of this technique in the subaxial cervical spine and the thoracic region. 3,5,11,12,14,15 Although cadaveric and CT-based analyses have been performed to assess the feasibility of TLS placement at C-2, there is limited information in the literature regarding the critical proportions of the upper thoracic laminae as they relate to the use of TLS. 2,7,24 In this study, CT scans were used to estimate screw size and placement in the upper thoracic spine, and we found that the average estimated TLS screw length at T-1 (33.4 mm) was 5.8 mm longer than at T-2 (27.6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few clinical reports in children. 4,22,28 In this study we restrict our analysis to children 5 years of age or younger. We consider these younger children to be the most challenging due to the factors described above.…”
Section: Discussionmentioning
confidence: 99%
“…There has not, however, been a report of the use of translaminar screws in the pediatric subaxial cervical spine except in association with Klippel-Feil deformity. [13][14][15] Therefore, the applicability of this technique to the general pediatric population is not known.…”
mentioning
confidence: 99%